Ideal Formulation of Extraordinary Legal Remedies Review By The Public Prosecutor From The Perspective of Justice and Legal Certainty - Krisna Murti; Fauzie Yusuf Hasibuan; Maryano Maryano (Asian Journal of Social and Humanities, 2024)
One of the crucial issues of legal problems that is still a pro and con in society is the extraordinary legal effort of judicial review by the public prosecutor. The research research is to analyze the implementation of the submission of extraordinary legal efforts of judicial review by the public prosecutor against criminal cases based on statutory regulations and to analyze and find the formulation of the ideal criminal case review system by the public prosecutor to realize justice and legal certainty in Indonesia. This research uses a type of normative juridical legal research. Research that uses a philosophical approach, a statutory approach, a case approach and a comparative approach. The sources of legal materials collected are analyzed descriptively to answer the research problems. The results of this study conclude that the Implementation of the submission of extraordinary legal efforts of judicial review by the Public Prosecutor against criminal cases based on statutory regulations has not achieved justice and legal certainty. In practice, the addition of the prosecutor's authority to file a judicial review as stipulated in Article 30C letter h and the Explanation of Article 30C letter h of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia cannot be implemented because it is considered contrary to the 1945 Constitution.